Wartime Housing Limited, 1941 - 1947: Canadian Housing Policy at the Crossroads - Wade, Jill (Urban History Review / Revue d'histoire urbaine, 1986)
Between 1941 and 1947 a federal crown corporation called Wartime Housing Limited (WHL) successfully built and managed thousands of rental units for war workers and veterans. WHL represents a directly interventionist approach to housing problems and demonstrates that the federal government could efficiently meet social needs by participating in housing supply. Though the Advisory Committee on Reconstruction recommended a national, comprehensive housing program emphasizing low-rental housing, the federal government initiated a post-war program promoting home ownership and private enterprise and, in the process, neglected long-range planning and low income housing. In addition, during the late 1940s, WHL's stock of affordable housing was privatized. This market-oriented perspective hindered advances in postwar housing policy in the same way that, for decades, the poor law tradition blocked government acceptance of unemployment relief. This paper reviews the housing record of WHL and examines the federal government's failure to redirect WHL's expertise into a permanent low-rental housing agency at the war's end.